PENGARUH PEMBERIAN AGRICARIVIT® TERHADAP JUMLAH LEUKOSIT DAN DIFERENSIAL LEUKOSIT AYAM BROILER - , RAHAYU SASMITA DEWI; , Dr. drh. Agustina Dwi Wijayanti, MP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Agricarivit® is the product combination of multivitamin, the electrolyte and l-carnitine that serves help metabolic processes. Giving Agricarivit® supplement on broilers are expected improve the carcass production because broiler has good genetics in it. The purpose of this study was to know the effect of Agricarivit® to white blood cell (WBC) count and leukocyte differentials of broiler chickens. The research using a hundred chickens were divided into four groups, raised since day old chick (DOC) till 35 day old, group one was treatment by 2 doses gram/l, group two is treatment by 4 doses gram/l, group three is treatment by 6 doses gram/l, and control group. Agricarivit® given in stage as follows on day 1 to day 4, 11 to 15, and the last day 21 to 25. Grating Agricarivit® performed on morning and afternoon. The results showed that the administration of Agricarivit® did not effect the WBC count and leukocyte differentials.